Eleven Primary Melanomas, Colon Cancer, and Atypical Nevi in the Same Patient: A Case Report and Literature Review - Lea Juul Nielsen; Lisbet Rosenkrantz Hölmich (Case Reports in Dermatological Medicine)
Background. As the incidence of cutaneous malignant melanoma increases in the Caucasian population, an increasing population of melanoma survivors is at risk of developing multiple primary melanomas (MPM) as well as secondary primary cancers. Objective. To present a case of a patient with atypical nevi, 11 primary melanomas over 33 years, and colon cancer and to review the literature on multiple primary melanomas, atypical nevi, and correlation of nonmelanoma cancers. Conclusion. The literature indicates that patients with MPM are not uncommon, although 11 primary melanomas are rarely described, that patients with MPM may have a better survival than patients with single primary melanoma, that atypical nevi are a risk marker of not only melanoma in general but also MPM, and that melanoma patients have a significantly increased risk of developing nonmelanoma skin and other cancers, which may be even higher for patients with MPM.